Efek Ekstrak Metanol Daun Engkuduk Talun (Fagraea racemosa) pada Peroksidasi Lipid Secara In Vivo (Journal of Tropical Pharmacy and Chemistry, 2025)
Engkuduk talun plant (Fagraea racemosa) grows in East Kalimantan forest. Stages Extraction research of petroleum eter-cloroform-metanol from leaves, root skin, root, stem skin and Fagraea racemosaâ€™s stem toward radical 2,2-diphenyl-1-picrylhydrazil (DPPH) is proven that the extract of methanol leaves have the strongest scavenger effect, this can be interpreted that the leaves have the strongest antioxidant potency from all plant parts that have been examined.  The given single dose 1 gram/kg b.w of the methanol extract from Fagraea racemosa leaves do not caused the death at the female Wistar rats. On the inhibitor test of forming MDA of ratâ€™s liver the very high of absorbance value has accurred on control by CCl4 ( 0.508 Â± 0.039 ), significant if compared to CCl4 added with the vitamin E ( 0.224 Â± 0.006 ) and CCl4 added with three doses of methanol extract from the Fagraea racemosaâ€™s leaves ( p=0.000 )